2020
DOI: 10.1007/s40123-020-00281-7
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Follow-Up of Excimer Laser Photorefractive Keratectomy: A Retrospective Observational Study

Abstract: Introduction: Photorefractive keratectomy (PRK) was introduced in the late 1980s to correct myopia. The purpose of this study was to assess its long-term efficacy and safety, analyzing patients with at least 20-year follow-up. Methods: This retrospective observational study was carried out on 85 eyes of 54 patients (33 females) that underwent PRK between 1991 and 1998 (mean age 32.62 ± 9.74, range 18-55 years). Both preoperatively and postoperatively, patients underwent a complete ophthalmological evaluation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…Das manifeste SE lag bei 86 % der Augen nach 10 Jahren innerhalb von ± 1,0 dpt der Zielrefraktion. Die Background Photorefractive keratectomy (PRK) was introduced in the 1980s to correct myopia and subsequentially different commercial laser systems and treatment algorithms have evolved [1,2]. Advantages of PRK over other refractive methods such as laser in situ keratomileusis (LASIK) include less dry eye symptoms, postoperative corneal ectasias, and avoidance of flap-related complications [2].…”
Section: Resultsmentioning
confidence: 99%
“…Das manifeste SE lag bei 86 % der Augen nach 10 Jahren innerhalb von ± 1,0 dpt der Zielrefraktion. Die Background Photorefractive keratectomy (PRK) was introduced in the 1980s to correct myopia and subsequentially different commercial laser systems and treatment algorithms have evolved [1,2]. Advantages of PRK over other refractive methods such as laser in situ keratomileusis (LASIK) include less dry eye symptoms, postoperative corneal ectasias, and avoidance of flap-related complications [2].…”
Section: Resultsmentioning
confidence: 99%
“…Limited studies reported long-term (one-decade or more) results of excimer laser surface ablation procedures including LASIK and PRK for the correction of myopia. 1 2 3 4 5 6 7 In a 12-year study of LASIK for moderate-to-high myopia, Ikeda et al 1 found a refractive regression of 0.7 D from 3 months to 12 years, postoperatively. They found a significant correlation of refractive regression with the changes in keratometry, but not with the changes in CCT from 3 months to 12 years.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Similarly, a recent retrospective study reported the safety of 1.00 and the efficacy of 0.63 at a 20-year follow-up after PRK. 7 Rajan et al 3 evaluated long-term refractive stability for myopic PRK and reported stability of refraction at 12 years, with no significant change in mean spherical equivalent between 1, 6, and 12 years and no late regression in the long-term. 3 Other studies of myopic refractive surgeries with PRK have also shown mild regression of <0.5 D at 10–16 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first studies performed in the 80's of last century, corneal refractive surgery (CRS) has been adopted as a leading method to correct refractive errors (1,2). Thanks to its reliability and effectiveness, today it is considered a worldwide diffuse and accepted method (3)(4)(5)(6)(7). It is well-known that the refractive effect is related to the corneal flattening and thinning, and several authors evaluated these induced changes (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%